EFISIENSI MODEL HORIZONTAL SUB-SURFACE FLOW CONSTRUCTED WETLAND DENGAN AKAR WANGI (VETIVERIA ZIZANIOIDES) PADA PENGOLAHAN LIMBAH CAIR TERNAK BABI - Purnama, I Gede Herry; Anggara, I Made Tejamurti (ARCHIVE OF COMMUNITY HEALTH, 2024)
Pig farms in Bali produce around 46 thousand tons of livestock waste each year. Pig liquid waste can endanger the environment and living things if it is directly discharged into waters or rivers without treatment. This study aims to determine the efficiency of setting aside the value of pig liquid waste parameters treated using the Horizontal Sub-Surface Flow Constructed Wetland model with Vetiveria Zizanioides based on BOD, COD, NH3-N, and pH parameters. This type of research is a true experiment with a pre-post design with control group design. The research stages were model preparation, trials, plant acclimatization and reactor start-up process. Wastewater sampling was carried out every test on days 6, 12, 18 and 25 with a detention time of 2 days. Wastewater was sourced from a pig farm located in Batubulan Village, Sukawati District. Sampling used grab sampling with a total of 108 test samples in the laboratory. Data were analyzed using descriptive analysis. The results showed that the overall removal efficiency of BOD, COD and NH3-N values in the replicate reactor was 19.34%, 18.26%, and 8.94% respectively and in the control reactor it was 24.68%, 24.67% and 3.51% and the range of pH values was around 7.44 - 8.35. It is concluded that this model is not efficient enough in treating pig wastewater according to each parameter so that various re-optimization efforts are needed if this model is applied to pig farms. Keywords: Efficiency, Constructed Wetland, Vetiveria Zizanioides, Pig Farm Wastewate